Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let A = $k[x_1, x_2, \ldots, x_n]$ and let $I_{\lambda}$ be an ideal of A.

Let J = $\sum_{\lambda \in \Lambda} I_{\lambda}$ be a finite sum. Show that $V(J) = \cap_{\lambda \in \Lambda} V(I_{\lambda})$.

It seems quite obvious that $V(\sum I_{\lambda}) \subseteq \cap I_{\lambda} $.

However, I am not at all sure where to start for showing the other inclusion. Ideas?

share|cite|improve this question

Suppose $x\in \cap_{\lambda\in\Lambda}V(I_\lambda)$, so $x$ vanishes on every polynomial $f_\lambda\in I_\lambda$ for any $\lambda\in\Lambda$. Let $f\in\sum_{\lambda\in\Lambda I_\lambda}$, so $f=\sum_{\lambda\in\Lambda} f_\lambda$ for some collection of polynomials $f_\lambda\in I_\lambda$. Then $f(x)=\sum_{\lambda\in\Lambda} f_\lambda(x)=\sum_{\lambda\in\Lambda}0=0$ so $x\in V(\sum_{\lambda\in\Lambda} I_\lambda)$. This proves $\cap_{\lambda\in\Lambda}V(I_\lambda)\subseteq V(\sum_{\lambda\in\Lambda} I_\lambda)$.

share|cite|improve this answer

Let $f\in J$, then $f=\sum_\lambda f_\lambda$, where the sum is finite and $f_\lambda\in I_\lambda$. Then, if $x\in \cap_\lambda V(I_\lambda)$, we have $$ f(x) = \sum_\lambda f_\lambda(x)=0 $$ since $x\in V(I_\lambda)$ for all $\lambda$, consequently $x\in V(J)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.